Vitamin D Status and Thyroid Autoantibodies in Autoimmune Thyroiditis - Koehler, Viktoria F.; Filmann, Natalie; Mann, W. Alexander (Hormone and Metabolic Research, 2019)
A lack of vitamin D seems to be related to autoimmune diseases including autoimmune thyroiditis (AIT). This study intends to determine the correlation between improvement of 25-hydroxyvitamin D [25(OH)D] levels and AIT in patients from an outpatient endocrine clinic in Frankfurt, Germany. This study included 933 patients with thyroid peroxidase antibodies (anti-TPO-Ab) ≥34 kIU/l, including most patients with clear AIT due to a concurrent sonographic evidence of reduced echogenicity. We performed clinical evaluation and laboratory analysis at five points in time within two years retrospectively. Due to a high dropout rate within the observation period, we excluded the last two time points from analysis. Data from 933 AIT patients revealed 89% having vitamin D deficiency or insufficiency [25(OH)D <75 nmol/l] with a median 25(OH)D level of 39.7 nmol/l. At baseline, a weak inverse correlation between 25(OH)D and anti-TPO-Ab was observed during winter (rs=–0.09, p=0.048*), but not during summer time (p>0.2). We discovered 58 patients having initially a 25(OH)D level < 75 nmol/l (median: 40.2 nmol/l), which improved over time to a 25(OH)D level ≥ 75 nmol/l (median: 83.2 nmol/l, p<0.0005***). Simultaneously, the median anti-TPO-Ab level showed a significant decrease of 25% from 245.8 to 181.3 kIU/l (p=0.036*). A significant reduction of the median anti-TPO-Ab level of 9% was also observed in the control group, which consisted of patients having constantly a 25(OH)D level <75 nmol/l. The result may suggest that in particular patients with 25(OH)D levels < 75 nmol/l benefit from an increase of 25(OH)D levels ≥ 75 nmol/l. Further prospective randomized controlled clinical trials are needed to finally evaluate if vitamin D has immunmodulatory effects in AIT.
Keywords: autoimmune thyroid disease; vitamin D deficiency; 25(OH)D